Biomarkers in Human and Environmental Health Risk Studies - Qasar Saleem,; Tanveer Akbar ,; Aqsa Salamat, (Journal of Basic & Applied Sciences, 2018)
Uncertainties in human health risk assessment, and the measuring on the impacts of contaminants have attracted great concern. Uncertainties, source-to-outcome, exposure assessment, hazard and risk characterisations are a number of techniques that have been applied to maximize results. Experts’ opinions and quantitative tools have been applied to narrow the gap between data and rules for regulatory purposes. Bio monitoring information, in vitro data streams and computational toxicology are major areas for human health risk assessment. A need for a biomarkers data bank is of utmost need to minimize uncertainties in the toxicological environmental human health risk assessment field.